2016
DOI: 10.1007/s00701-016-2934-x
|View full text |Cite
|
Sign up to set email alerts
|

Paroxysmal sympathetic hyperactivity in severe traumatic brain injury

Abstract: Presence of PSH in patients with severe TBI was associated with prolonged hospital stay, poorer DRS at discharge, more deaths, and unfavorable outcome. The number of symptoms of PSH had a significant effect on outcome at 6 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 16 publications
0
25
1
1
Order By: Relevance
“…Given that further assessment and inspection due to persistent symptoms is necessary in the treatment of patients with TBI, PSH-AM can help to avoid misdiagnosis, enhance diagnostic efficiency, save time, and reduce economic costs. The prospective predictive value of the PSH-AM tool has been confirmed in sensitivity/specificity analysis, showing higher sensitivity, though limited specificity (10). A recent retrospective analysis suggested that the incidence of diagnosed PSH cases in TBI patients was reduced from 32 to 18%, compared with previous studies, using this tool (59).…”
Section: Identification Of Pshmentioning
confidence: 82%
See 2 more Smart Citations
“…Given that further assessment and inspection due to persistent symptoms is necessary in the treatment of patients with TBI, PSH-AM can help to avoid misdiagnosis, enhance diagnostic efficiency, save time, and reduce economic costs. The prospective predictive value of the PSH-AM tool has been confirmed in sensitivity/specificity analysis, showing higher sensitivity, though limited specificity (10). A recent retrospective analysis suggested that the incidence of diagnosed PSH cases in TBI patients was reduced from 32 to 18%, compared with previous studies, using this tool (59).…”
Section: Identification Of Pshmentioning
confidence: 82%
“…Previous and recent cases provide evidence that PSH-AM can not only serve as reliable diagnostic criteria, but also stratify the severity of PSH (10,57). The tool is able to dynamically monitor the evolution of individual PSH patients' clinical status, and is also valuable in diagnosing PSH in different types of brain trauma [e.g., diffuse axonal injury; (57,58)].…”
Section: Identification Of Pshmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Prognosis PSH is associated with worse clinical outcomes after TBI, both short-term and long-term. 1,3,5,12,14 Prognosis is also worse in pediatric patients with TBI who have PSH. 35 Yet, it is unclear whether this association of PSH with worse prognosis is due to the preferential occurrence of PSH in patients with more severe brain injury (in which case PSH would be only a surrogate marker for disease severity rather than a factor influencing the prognosis per se) or to a direct detrimental effect of PSH on prognosis.…”
Section: Seminars In Neurologymentioning
confidence: 99%
“…2 Also, if untreated, PSH may worsen over time and may cause serious secondary complications. 3 While formal evidence on treatment interventions is scant and lacks methodological quality, PSH is a treatable disorder. Adjustments in supportive care and adequate pharmacological interventions can often substantially mitigate the condition.…”
mentioning
confidence: 99%